2013
DOI: 10.1007/s00438-013-0746-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased copy number at the HvFT1 locus is associated with accelerated flowering time in barley

Abstract: A precise regulation of flowering time is critical for plant reproductive success, and therefore, a better understanding of the natural variation in genes regulating the initiation of the reproductive phase is required to develop well-adapted varieties. In both monocot and dicot species, the FLOWERING LOCUS T (FT) is a central integrator of seasonal signals perceived by the leaves. The encoded mobile protein (florigen) is transmitted to the apical meristem where it induces flowering. The FT homolog in barley (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 53 publications
4
83
0
Order By: Relevance
“…Tammi. The Tammi allele for Vrn-H3 was shown to include four copies of HvFT1, which is associated with earlier transcriptional up-regulation of themselves (Nitcher et al, 2013). Therefore, it was considered that the spring allele Vrn-H3 (high expression of HvFT1) is epistatic to that of HvPhyC-e and HvPhyC functions in the same pathway as Vrn-H3.…”
Section: Discussionmentioning
confidence: 99%
“…Tammi. The Tammi allele for Vrn-H3 was shown to include four copies of HvFT1, which is associated with earlier transcriptional up-regulation of themselves (Nitcher et al, 2013). Therefore, it was considered that the spring allele Vrn-H3 (high expression of HvFT1) is epistatic to that of HvPhyC-e and HvPhyC functions in the same pathway as Vrn-H3.…”
Section: Discussionmentioning
confidence: 99%
“…In crops a causal relationship between copy number and phenotypic variation linked to single genomic regions has been firstly demonstrated for the barley Bot1 boron transporter gene (Sutton et al 2007). Later on, the study of the soybean Rhg1 cyst nematode resistance locus (Cook et al 2012), of the maize efflux transporter MATE1 (Maron et al 2013), and the barley flowering time determinant FT1 (Nitcher et al 2013) showed that different phenotypes in evolutionary distant plant species could be ruled by CNV gene dosage effects. A similar phenomenon was also hypothesized for the FR-H2 locus by .…”
Section: Introductionmentioning
confidence: 98%
“…Structural variation can lead to CNV of genes, which, in turn, affects gene dosage and transcription strength (Stranger et al, 2007;Schlattl et al, 2011;Massouras et al, 2012;Haraksingh and Snyder, 2013). In plants, many examples exist for the copy number of a gene or genome segment associated with phenotype changes (Cook et al, 2012;Li et al, 2012;Maron et al, 2013;Nitcher et al, 2013), and genome-wide CNVs appear to predict phenotypes to some extent Muñoz-Amatriaín et al, 2013). The S. parvula genome is characterized by a higher copy number of genes associated with transporter activity (Dassanayake et al, 2011a).…”
Section: Genome Structure Shapes the Transcriptomementioning
confidence: 99%
“…For example, the regulation of flowering time, crucial for reproductive success in a narrow seasonal window, has been associated with copy numbers of FLOWERING LOCUS T1 (FT1) genes in barley (Hordeum vulgare; Nitcher et al, 2013). Increased copy numbers of related genes or gene clusters have conferred adaptive traits such as an enhanced defense against pathogens (Keeling et al, 2008;Cook et al, 2012) and metal ion tolerance (Hanikenne et al, 2008;Craciun et al, 2012;Maron et al, 2013) in various plant species.…”
mentioning
confidence: 99%